GERAKAN NGAJI FIQIH: IKHTIAR MENINGKATKAN RELIGIOSITAS ANAK DI DUSUN MOJOSARI, GUNUNGKIDUL - Setiadi, Wisnu (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
Religiosity is directly proportional to children's behavior. One of the basic things in children's behavior is influenced by religious understanding. This understanding can be responded to through the ngaji fiqh movement in the chapter on ablution and prayer which aims to enable children to increase their religiosity to God. The researcher in his article used descriptive-qualitative research with a product development method approach to teaching programs through Research and Development in the development of the 4D model. The product in question is the ngaji fiqh program for children that is adjusted to the needs of the community. The results of the community service research in Mojosari Hamlet through the ngaji fiqh movement program can bring benefits to children, namely better and correct ablution and prayer, creating adaptation to prosper the mosque, and awareness of the role of parents to their children. In the implementation that has gone well, the researcher hopes that this program can be continued through similar community service by the campus as an implementation of the Tridharma of higher education. In line with expectations, to policymakers in the regions they do not remain silent in forming a young generation of religious hamlets so that they behave according to community norms and Islamic values.